Strategi Penyelamatan Pembiayaan Bermasalah Pada Pembiayaan Murabahah Bank BNI Syariah Cabang Bogor - Ari Zulfikri; Ahmad Sobari; Syarifah Gustiawati (Prodi Perbankan Syariah FAI UMT, 2019)
In Islamic banking institutions, the term problem financing is not something foreign is heard. Almost all conventional and sharia banking institutions experience this, because not a few banking institutions are hampered by their growth and even have to stop their operations because they cannot overcome this problem. The Islamic banking sector is led to have a strategy in dealing with problem financing. Referring to the Bogor Branch of NPF Bank BNI Syariah data in 2016 (3.42%), 2017 (2.78%), 2018 (1.58), it is known that the NPF value at the Bogor Branch of BNI Syariah has decreased (considered good) , because it is still below the maximum standard NPF value set by Bank Indonesia (5%). Financing at the Bank BNI Syariah Bogor Branch continues to increase every year and the financing that is dominated is Murabahah financing. To achieve a good NPF value, the Bank BNI Syariah Bogor Branch uses a strategy to overcome problem financing, namely stay strategy and exit strategy. However, for the stage of saving the problematic financing the strategy used is to stay a strategy through financing restructuring efforts.